Does lubrication of the vaginal speculum reduce pain during a gynecologic oncology examination?. (January 2015) - Gungorduk, Kemal; Ozdemir, Aykut; Gökçü, Mehmet; Sancı, Muzaffer
Abstract: Objective: To evaluate the effectiveness of lubricant gel for reducing pain during a vaginal speculum examination (SE) in patients with gynecologic cancers. Study design: This non blind randomized controlled trial included 200 women who underwent SE for post-treatment surveillance. One-hundred patients each were allocated to the water and lubricant gel groups. All patients were asked to score their pain during speculum insertion, dilatation, and extraction using a visual analog scale (VAS). Pain intensity during speculum insertion was the primary outcome measure. Results: There were no statistically significant differences in demographic characteristics between the water ( n  = 97) and lubricant gel ( n  = 98) groups. The VAS pain scores obtained during all phases of the SE were significantly lower in the lubricant gel group compared with the water group during the insertion (3.95 ± 1.57 vs. 5.28 ± 1.71, P  < 0.001), dilatation (5.96 ± 1.48 vs. 6.74 ± 1.69, P  < 0.001) and extraction phases (2.60 ± 1.17 vs. 3.50 ± 1.25 P  < 0.001). When a separate analysis was performed for the patients who underwent radiation therapy, the mean VAS pain scores were significantly lower in the lubricant gel group during the insertion (4.46 ± 1.45 vs. 6.22 ± 1.79, P  < 0.001), dilatation (6.31 ± 1.66 vs. 7.52 ± 1.61, P  = 0.002) and extraction phases (2.68 ± 1.31 vs. 3.66 ± 1.06, P  = 0.001). Conclusion: The use of speculum lubricant gel significantly decreased pain during the SE in gynecologic oncology patients.